2015
DOI: 10.1007/s10862-015-9501-2
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Validation of the Reactive-Proactive Aggression Questionnaire (RPQ) Using Four Large Samples from the US, Hong Kong, and China

Abstract: This is the first study to assess the validity the Chinese version of the Reactive and Proactive Aggression Questionnaire (RPQ). The RPQ was administered to 11 year-old participants in the China Jintan Child Cohort Study, a population-based longitudinal study of 1352 children. Similar to other studies, a two-factor solution with one reactive and one proactive subscale best described the data. Overall, the Chinese version of the RPQ had good construct validity, internal consistency, and test-retest reliability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
5
18
0
Order By: Relevance
“…It was confirmed that the structure with two interrelated factors and residual covariances has the best adjustment indicators regarding the other models, that is, aggression is constituted as a construct that can be measured by the RPQ from two dimensions, reactive and proactive aggression (Andreu et al, 2009;Raine et al, 2006), which allow the assessment of mixed aggression (Penado et al, 2014), as both are correlated (r=.663, p<.001). Also, this confirmed model coincides with previous cross-cultural reports (e.g Brugman et al, 2017;Fung et al, 2009;Pechorro et al, 2017;Tuvblad et al, 2016;Dinić & Raine, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was confirmed that the structure with two interrelated factors and residual covariances has the best adjustment indicators regarding the other models, that is, aggression is constituted as a construct that can be measured by the RPQ from two dimensions, reactive and proactive aggression (Andreu et al, 2009;Raine et al, 2006), which allow the assessment of mixed aggression (Penado et al, 2014), as both are correlated (r=.663, p<.001). Also, this confirmed model coincides with previous cross-cultural reports (e.g Brugman et al, 2017;Fung et al, 2009;Pechorro et al, 2017;Tuvblad et al, 2016;Dinić & Raine, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Currently, different studies have reviewed and obtained a solution of two correlated factors that have demonstrated the best fit, even in cross-cultural validations, findings that support the conceptual differences of PA and RA (e.g. Brugman et al, 2017 ; Fung, Raine, & Gao, 2009 ; Pechorro, Kahn, Ray, Raine, & Gonçalves, 2017 ; Tuvblad, Dhamija, Berntsen, Raine, & Liu, 2016 ). These differenes have not been reported in Latin America to date, particularly in studies of the structural confirmation of this construct, much less on its specific population variations.…”
Section: Introductionmentioning
confidence: 99%
“…However, the current study additionally examined alternative factor solutions by using an EFA, which, to our knowledge, has never been used before regarding the RPQ in an adult sample. Previously, other factor solutions have been investigated with respect to children (Tuvblad, Dhamija, Berntsen, Raine, & Liu, ). Regarding adults, on the other hand, previous research mainly focused on investigating a one‐factor model in comparison with a two‐factor model.…”
Section: Discussionmentioning
confidence: 99%
“…The RPQ contained 12 items measuring proactive aggression (e.g., “Had fights with others to show who was on top”), and 11 items on reactive aggression (e.g., “Reacted angrily when provoked by others”). The reliability and validity of the Chinese versions of the scale are adequate (Quan et al, 2019; Tuvblad, Dhamija, Berntsen, Raine, & Liu, 2016; Zhang, Jia, Chen, & Zhang, 2014). Cronbach's α in the current sample at Time 1 was .83 (Reactive Scale) and .88 (Proactive Scale), and it was .81 (Reactive Scale) and .88 (Proactive Scale) at Time 2.…”
Section: Studymentioning
confidence: 99%